Plague times: scientific internationalism and the Manchurian plague of 1910/1911 - Knab, Cornelia (Itinerario, 2011)
Among epidemic diseases, plague is particularly charged with historical memory and ominous cultural connotations. In many parts of the world, plague's seemingly mysterious origins, its gruesome ways of spreading, and its powers of devastation have raised it to a symbol of evil. In several languages, the word “plague” itself has become synonymous with scourge and universal disaster over the centuries. However, plague is not only a disease from the remote past; it also exemplifies the biological globalisation of modern times, highlighting at once socio-biological phenomena, global connectedness, and other dimensions of modernity. In particular, outbreaks of the so-called third plague pandemic from the late nineteenth to the mid-twentieth century made the disease an oppressive reality in many regions of the world.
Published online by Cambridge University Press: 14 March 2012
Gesehen am 26.09.2022